(untitled) (Revista de Artes Marciales Asiáticas, 2016)
Technical-tactical and physiological demand analyses of wrestling combats are important because they reveal essential information for the development of contextual training and specific physical preparation of wrestlers. Therefore, the aim of this review is to describe the characteristics of wrestling combats in freestyle, female and Greco-roman styles. The time-motion analysis presented in this article is the main component to carry out inferences on intensity and effort: pause ratio of combat actions. After rules modification in 2013, wrestling combats showed quicker and more diversified actions, especially in the lighter categories. For Greco-roman wrestling, most studies showed takedowns as the most effective techniques in World competitions for the period 2009-2011. For the same period, foot/leg techniques were the most effective in female and freestyle wrestling, followed by takedown attacks. Recent analyses, developed after 2013 rules modification, showed that the decisive offensive actions were applied on foot and in par terre situations – especially gutwrenches techniques and derivatives of suplex movements. The knowledge on the determinant and predominant actions of wrestling combats can be applied in future research, as well as can be used practically for training, physical preparation and assessments of similar combat actions. It also allows interventions to prevent injuries resulting from technical and tactical wrestling actions.